Global trends in educational policy - Baker, David, 1952 Jan. 5-; Wiseman, Alexander W., 1968- (International perspectives on education and society ;, 2005)
This volume of "International Perspectives on Education and Society" highlights the valuable role that educational policy plays in the development of education and society around the world. The role of policy in the development of education is crucial. Much rests on the decisions, support, and most of all resources that policymakers can either give or withhold in any given situation. The eleven chapters in this volume present persuasive arguments that the internationalization of educational policy has a wide and irreversible effect on schooling and society around the world. Indeed, educational policy is intricately woven into the development of societies. Chapters range from empirical investigations of educational policies impact on national schooling trends to narrative histories of policy-important multilateral organizations and professional societies. In addition to the editors, the contributors include Sheng Y. Cheng, Holger Daun, Diane G. Gal, Stephen P. Heyneman, W. James Jacob, Nancy O. Kendall, Veronica Martini, Mary Ann Maslak, Diane B. Napier, Jordan Naidoo, and David N. Wilson.